Evaluation Tools for Physical Activity Programs for Childhood Cancer: A Scoping Review. (May 2020) - Shank, Jena; Chamorro-Viña, Carolina; Guilcher, Gregory M. T.; Langelier, David Michael; Schulte, Fiona; Culos-Reed, S. Nicole
Research on the benefits of physical activity (PA) in childhood cancer has been translated into a handful of community-based programs. However, to foster further translation, an understanding of how to evaluate participant outcomes would be beneficial to provide feedback to participants and stimulate future research. Such a review would provide a summary of acceptable tools for work in this area. The purpose of this scoping review was to identify the evaluation tools that have been used in PA/exercise studies or programs for childhood cancer. This review was conducted using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Studies included in the review used physical and psychosocial evaluation tools within PA and exercise programs or research for childhood cancer. In addition, studies with measures of health behavior such as PA levels and activities of daily living were included. Tools that assessed physical fitness and physical performance were excluded. Information on the types of evaluation tools used, mean age of participants, and type of cancer was extracted. Psychometric properties of each evaluation tool are reported. The most commonly assessed patient outcomes were motor performance, fatigue, well-being, functional mobility, and quality of life. Less commonly reported patient outcomes were hope, self-efficacy, and self-perception. None of the evaluation tools reported in the PA/exercise and pediatric oncology literature assess physical literacy. This review was the first step in a knowledge translation process, identifying evaluation tools that have been used in PA/exercise programs in childhood cancer survivors, that will guide the development and evaluation of current and future community-based programs.